Realizing Society 5.0 to Face the Industrial Revolution 4.0 and Teacher Education Curriculum Readiness in Indonesia - Aprilisa, Ema (Proceeding International Conference on Science and Engineering, 2020)
Educational institutions have to aware about digital transformation, which is immediately responded with the concept of Industrial Revolution 4.0 or Industry 4.0 as a national strategic initiative from the German government through their Ministry of Education and Research. Meanwhile, Japan also formulated the concept of Society 5.0 aims to create a human-centric society in the era of technology and also to tackle some of negative aspects comes with the rapid change. Therefore, educational institutions need to check their curriculum to cope up with the transformation. This research is to conduct an analysis of teacher education program’s curriculum, especially Bachelor of Education in Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta. The analysis focus on the correlation between Program Learning Outcome (PLO) with the needs of Industrial Revolution 4.0 era and to realize Society 5.0. It is also highlighting the fact that as a future teacher, the college students of the program need some spesific skills. So that one day, they are able to teach with suitable strategy for the era. The results of this study indicate that some PLOs are in accordance with top ten skills demand in 2022 which is considered to be in line with the essential skills to face Industrial Revolution 4.0 and realize Society 5.0. In fact, the top ten skills demand in 2022 is suspected to have been covered by the PLO formula of the curriculum applied by Bachelor of Education in Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta. This provides a glimmer of hope for the future of education in Indonesia, but we still emphasizing the need to ensuring every course supports PLO achievement.